2019
DOI: 10.1017/jpa.2019.3
|View full text |Cite
|
Sign up to set email alerts
|

Family Naticidae (Gastropoda) from the Upper Jurassic of Kutch, India and a critical reappraisal of taxonomy and time of origination of the family

Abstract: Naticid taxonomy is in a state of flux owing to non-descript shell morphology and frequent convergence. Inadequate preservation of naticid body fossils has further complicated the matter in determining the true affinity and the exact time of origin of the clade. As a result, a plethora of classificatory schemes of naticid phylogeny and times of origin has been proposed. In many previous studies, true naticid affinities of fossils have been sought based on single or a few morphological characters, which are sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 29 publications
1
28
0
1
Order By: Relevance
“…Recently, Das et al . (2019) reported naticids from the Oxfordian of Kachchh, India, which would be the earliest occurrence of naticids although the preservation of the specimens seems insufficient for a safe attribution to Naticidae. The identity of the drilling predator(s) before the Late Jurassic is still unknown (Harper et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Das et al . (2019) reported naticids from the Oxfordian of Kachchh, India, which would be the earliest occurrence of naticids although the preservation of the specimens seems insufficient for a safe attribution to Naticidae. The identity of the drilling predator(s) before the Late Jurassic is still unknown (Harper et al .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Das et al . (2019) documented the occurrence of naticid gastropods together with naticid‐type drill holes from the Oxfordian of Kachchh and suggested naticids as the culprit for the drill holes in gastropod and bivalve shells found there. This would extend the record of naticids back to the Upper Jurassic.…”
Section: Introductionmentioning
confidence: 99%
“…Morphologically, naticids have a very simple shell, and as discussed by previous authors, external shell characters may not be sufficient to segregate the members of this family (Bandel 1999;Das et al 2019). Perhaps for this reason, several workers in the past related naticids with other diverse gastropod families such as the Ampullinidae, Calyptridae, Cypridae, Littorinidae, Neritidae, and Xenophoridae (Bandel 1999;Kase and Ishikawa 2003;Strong 2003;Colgan et al 2007; for reviews, see Aronowsky 2003;Hülsken 2008).…”
Section: Discussionmentioning
confidence: 99%
“…To counteract problems related to convergent shell characteristics, some authors have suggested the use of soft part anatomy (Aronowsky 2003) and molecular coding (Hülsken et al 2006(Hülsken et al , 2008(Hülsken et al , 2012. However, soft parts are not preserved in the fossil record, and thus their use is limited to extant taxa only (for a similar argument, see Das et al 2019). Das et al (2019) suggested a few subfamilybased hard part characters that can be used to distinguish among the four subfamilies-Naticinae, Polinicinae, Sininae, and Gyrodinaealthough clear distinctions could not be made.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation